PENGARUH PENERAPAN PENDEKATAN PROSES BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS DESKRIPSI DI SD - Wulansari, Endang Wahyuni; Halidjah, Siti; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purposeof this study was to analyze the influence of the application of process approach assisted media images on the description writing skills for third grade students at Elementary School 15 Sungai Raya. The research method used was an experiment, a form of Quasi Experimental type of non equivalent group design.The population is all students from three classes totaling 65 people, while the sample is class 3A and class 3B which amounts to 65 people. The sampling technique uses purposive sampling. The technique used is direct observation and measurement. Data collection tools in the form of observation sheets and tests.The results of data analysis are, the average score of the experiment class post-test is 68,27 and the control class is 62,92. Based on the results of the t-test calculation obtained by tcount 2.37>ttable 1.98, then Ha is accepted, which means there is ainfluence on the application of process approach on the description writing skills. From the calculation of the effect size, obtained (ES) of 0,62 with medium criteria. Means the application Â of the application of process approach has a medium influence on the description writing skills for third grade students at Elementary School 15 Sungai Raya.Key words : Description Writing Skills, Influence,Â  Process Approach